Native fish losses due to water extraction in Australian rivers: Evidence, impacts and a solution in modern fish‐ and farm‐friendly screens. (17th May 2021) - Boys, Craig A.; Rayner, Thomas S.; Baumgartner, Lee J.; Doyle, Katherine E.
Summary: The diversion of water from rivers removes millions of fish from Australian waterways each year. Modern diversion screens are available that can reduce fish losses by 90% and stop debris entering irrigation systems. Uptake of this technology in the United States has protected fish and infrastructure. However, application in Australia has been poor and both the problem and its solution continue to be overlooked. To address this, we summarise multiple lines of evidence of fish losses in Australia and propose a way forward. Large losses of fish at diversions have been reported for close to a century, providing compelling evidence of population‐scale impacts on native fish. We discuss the solution, outlining the progress being made to bring modern screening technology to Australia, including a social learning framework to improve how water is diverted and focussing on collaboration between the fisheries, agriculture and engineering sectors, and underpinned by science. We conclude that uptake of modern screens will rely on dialogue moving past whether a problem or solution exists, to the following: how screening can be better integrated with water and environmental management; where investment should be prioritised; and how screening could be funded. If Australia gets this right, substantial benefits can be realised, saving millions of native fish every year, bolstering native fish recovery programmes, reducing ongoing costs for water users and enhancing the economic and social value in regional areas by boosting manufacturing, service industries, tourism and recreational fisheries.